2006
DOI: 10.1111/j.1365-294x.2006.02930.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative phylogeography of woodland reptiles in California: repeated patterns of cladogenesis and population expansion

Abstract: The ultimate goal of comparative phylogeographical analyses is to infer processes of diversification from contemporary geographical patterns of genetic diversity. When such studies are employed across diverse groups in an array of communities, it may be difficult to discover common evolutionary and ecological processes associated with diversification. In order to identify taxa that have responded in a similar fashion to historical events, we conducted comparative phylogeographical analyses on a phylogeneticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
106
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(116 citation statements)
references
References 94 publications
(145 reference statements)
8
106
0
Order By: Relevance
“…Many phylogeographic studies of species in California have found high levels of cryptic genetic structure, similar to what we found in A. lugubris [2,3,9,15]. Below we compare the geographic distribution of our mtDNA clades in relation to vicariance events, as well as to physical/climatic barriers to dispersal in other species.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Many phylogeographic studies of species in California have found high levels of cryptic genetic structure, similar to what we found in A. lugubris [2,3,9,15]. Below we compare the geographic distribution of our mtDNA clades in relation to vicariance events, as well as to physical/climatic barriers to dispersal in other species.…”
Section: Discussionmentioning
confidence: 80%
“…California has been the focus of a large number of phylogeographic studies, largely because of the great diversity of species inhabiting the state and the complex geological processes active in the region [2][3][4]. The California floristic province has been designated as one of the world's top 25 hotspots of biodiversity and the state of California encompasses 70 % of this province [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Somewhat separate from the marine embayment, another historically important isolating barrier for small vertebrates in Central California is the Kern River (Jockusch et al 1998;Jockusch and Wake 2002;Feldman and Spicer 2006). The Kern River is one of the biggest rivers in the southern Sierra Nevada and used to empty into the San Joaquin embayment and, after the Pliocene, into the Buena Vista Lake.…”
Section: Discussionmentioning
confidence: 97%
“…A few reptile and amphibian species have genetic lineages endemic to Central California, e.g., Pacific pond turtles (Spinks and Shaffer 2005), alligator lizards (Feldman and Spicer 2006), and slender salamanders (Wake 2006), but it is not as common a pattern as the north-south break. Moreover, as far as we know, the presence of deep genetic lineages within the San Joaquin Valley and Carrizo Plain (lineages B and C) is a pattern unique to Anniella.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation